Allelopathic bioactivity of fresh and infused aqueous extracts of Brazilian cherry (Eugenia uniflora L.) on lettuce and maize (Acta Scientiarum. Biological Sciences, 2018)
This study aimed to analyse the allelopathic bioactivity of fresh and infused aqueous extracts of Brazilian cherry leaves on the germination of lettuce and the initial development of maize. Brazilian cherry leaves were used to prepare a fresh aqueous extract (200 g L-1) and an infused extract (100 g L-1), which were diluted to concentrations of 0.4, 0.8, 1.2, 1.6 or 2.0% w/v. The variables evaluated in lettuce were the germination rate (GR), germination time index (GTI), germination speed index (GSI) and root length (RL). To determine the effect on the initial development of maize, we measured the shoot (SL) and root (RL) length. The experimental design included a factorial 2 Ã— 5 design (two extracts and five concentrations), in addition to a control treatment (no extract). In general, the allelopathic bioactivity differed between the fresh and infused extracts. The fresh extract was more phytotoxic for the GR and RL of lettuce. Some beneficial results were observed for the infused extract, including an increase in the RL of lettuce and SL of maize. These effects were dependent on the extract concentration. Thus, there is evidence that Brazilian cherry extracts have allelopathic bioactivity.